Oil palm EFB supported solid acid catalyst for esterification reaction: Optimization and parametric effects study - Krishnan S.G.; Pua F.L.; Palanisamy K.; Jaafar S.N.S. (American Institute of Physics Inc., 2023)
An acid esterification of free fatty acid (FFA) from high acid content palm oil and methanol has been investigated. This study describes an optimization study on the esterification reaction using Oil Palm EFB supported solid acid catalyst. A statistical experimental design of L9 orthogonal array using Taguchi method was implemented to optimize the esterification reaction conditions to maximize FFA conversion. Three main reaction conditions include methanol to oil molar ratio, reaction duration (min) and percentage of catalyst loading were investigated. Based on the results, the optimum conditions were obtained as follows: molar ratio of methanol to oil of 30:1, reaction duration of 120 min, catalyst loading of 5 wt%, constant temperature of 60 C. At these reaction conditions, the highest FFA conversion was achieved with 87.20%. Notably, methanol to oil molar ratio has the most significant effect on the FFA conversion followed by reaction duration. Catalyst loading has minimal effect on FFA conversion throughout the reaction. Thus this study showed that methanol to oil molar ratio has the strongest influence in FFA conversion. 2019 Author(s).